ULTRASONIC EXCISION OF INFECTED MESH IMPLANTS AFTER HERNIOPLASTY (CLINICAL CASE) - Vladimir S. Panteleev; Vitaliy A. Zavarukhin; Mariya P. Pogorelova (Креативная хирургия и онкология, 2017)
Introduction. Deep wound surgical infection that occurs after installing mesh implants, with ventral hernia, is a serious problem that does not have a definite approach to its solution.Materials and methods. The work clinically demonstrated effectiveness of originally developed method to surgically remove the infected mesh implants after hernioplasty. The developed method of surgical intervention when deleting infected mesh implants is to excise the post operational scar together with adipose tissue within healthy tissues, to detach and  subsequently separate the previously installed implant from the abdominal wall by the destruction of connective-tissue adhesions using ultrasound. The surgery technique provides for the devastating effect of ultrasonic waves on the connective tissue through a liquid antiseptic - 0.2% solution of water chlorhexidine of bi-gluconate.Results. The findings show that the use of a new original method facilitates the effective removal of the mesh implant using ultrasonic cavitation from adhesions with tissues of the organism in the field of surgery without excision, traumatizing and bleeding, and also promotes wound sterilization.Conclusion. Thus, the developed method allows eliminating infected implants using ultrasound, minimizing trauma of the underlying soft tissues, which means that it preserves the possibility to keep hernial defect sutured with first row of sutures, which helps to prevent relapse of herniation.